THE EFFECT OF GREEN ACCOUNTING AND ENVIRONMENTAL PERFORMANCE ON FIRM VALUE (CASE STUDY OF ENERGY COMPANIES IN THE COAL SUB-SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE IN 2022-2024) - Dewi, Ni Putu Ayu Risna; Diatmika, I Putu Gede; Devi, Sunitha; Yuniarta, Gede Adi (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
Global shifts towards sustainable business practices have put great pressure on industries with high environmental impacts, especially the coal sector. This study aims to analyze the effect of green accounting and environmental performance on the value of coal companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. This study uses a quantitative approach with a purposive sampling method, namely a sampling technique based on certain criteria set by the researcher so that the samples taken are relevant to the research objectives, secondary data are collected from financial reports, sustainability reports, and PROPER ratings. The results of the regression analysis show that green accounting has a positive and significant effect on company value (B = 1.546; p = 0.031), indicating that environmental transparency is valued by the market. In contrast, environmental performance does not show a significant effect (B = -0.108; p = 0.481), indicating a paradox between disclosure and actual results. These findings contribute to legitimacy theory and stakeholder theory, and offer strategic guidance for companies, investors, and policy makers in facing the energy transition in Indonesia.